KONSTRUKSI KIAI OLEH MASYARAKAT DESA GADU TIMUR KECAMATAN GANDING KABUPATEN SUMENEP - Anis Kurli (Jurnal Komunikasi, 2015)
The purpose of the study is to describe the Kiai’s Construction made by thesociety of Gadu Timur Village. This society belongs to a community wich ishas tight relationship in the social of Kiai. Futhermore, the study is expectedto provide a description of Kiai roles in rural society which is known as nonformalleader that is respectedand honoredby any level of society. The study applies qualitative descriptive analysis. The data collectingmethod is conducted through documentation, interviews and observation.Informants are selected through purposive sampling method. Miles andHuberman’s technique is used as data analysis. Triangulation of data sourceis applied as data validity checker. The results of the study shows that Kiai construction made by the societyof Gadu Timur village are: Kiai as Ulama (Islamic leader), Kiai as rovingpreacher, Kiai as KiaiSembur, Kiai as Charismatic figure and Kiai as apolitical figure. Keywords: Construction, and Kiai’s Role.